Regional State-Owned Enterprises, Regional Heads, And The Pancasila Welfare State In A Deconstructive Perspective - Maria Fransiska Owa da Santo; Catarina Dewi Wulansari; Sentosa Sembiring; Ernesta Uba Wohon; Stefanus Don Rade (Riviera Publishing, 2025)
This research responds to the debate regarding the legal status of Regional Companies (Regional Companies) and the legal position of regional heads in their management. With a legal deconstruction approach, this study aims to find the fundamental meaning of the formation of a legal entity of a Regional Company, which is expected to provide legal certainty for local governments, communities, and third parties who want to collaborate. The method used is normative legal research with a focus on the discovery of law in concreto, which requires the analysis of previous legal norms. This study includes observations of the management of Regional Companies to understand the dynamics of the relationship between the legal status of Regional Companies, regional heads, and the principles of the welfare state in the context of economic development. The resulting legal arguments are expected to explain the dilemma of the legal status of Regional Companies which lie between public and private law, as well as their impact on the institutional, financial, and responsibility of regional heads. The analysis process is carried out by the method of systematizing legal materials in a descriptive manner, explicit explanations, and prescriptive improvements through legal interpretation.